PEMBELAJARAN MENULIS TEKS EKSPOSISI DENGAN MODEL PEMBELAJARAN BERBASIS MASALAH DI SMP - Wahyuni, Sri (Universitas Negeri Makassar, 2015)
This study aims to describe the processes and outcomes of learning to write text exposition using problem-based learning model. The research was designed to study the class action. The data used in this research is data such as the implementation process of observation, field notes, and documentation, as well as data evaluation results include the results of the test write text exposition using problem-based learning model. Data sourced from seventh grade students of SMP Negeri 2 Sabbangparu Wajo. The results showed that the exposition text writing skills has increased significantly.